2019
DOI: 10.31224/osf.io/5wy8s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fees and governance: Towards sustainability in water resources management at schools in post-apartheid South Africa

Abstract: Water scarcity is increasingly staking a claim next to energy as a threat to the sustainability of large cities, especially in developing countries with limited resources. The recent crisis brought on by Cape Town’s “Day Zero” drought created the impetus to expand on existing research on water demand management to include analysis of school usage patterns and key determinants thereof. With the effects of apartheid still visible in society and in school infrastructure coupled with the high water usage rates at … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Recent studies performed the most comprehensive analysis of water usage and management within schools in the Western Cape (Visser et al, 2021;Booysen et al, 2019a, b). This included investigating socio-economic effects, behavioural interventions and technical interventions.…”
Section: Related Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies performed the most comprehensive analysis of water usage and management within schools in the Western Cape (Visser et al, 2021;Booysen et al, 2019a, b). This included investigating socio-economic effects, behavioural interventions and technical interventions.…”
Section: Related Researchmentioning
confidence: 99%
“…Moreover, Section 21 schools are responsible to pay for their own upgrades, school materials, utility bills and maintenance Samuels et al (2020). These schools are allocated funding by the government, however, from observations made during previous studies this funding was found to be insufficient (Booysen et al, 2019a). In contrast, Section 20 schools are not charged monthly utility costs and are not responsible for their own maintenance.…”
Section: Overview Of Schools In Datasetmentioning
confidence: 99%
See 3 more Smart Citations